Mapping the Literature on Digital Payment: A Comprehensive Review and Bibliometric Analysis - Prashant Pareek; Nirmit Kansara (International Journal of Optical Innovations & Research, 2024)
This study essentially performs a comprehensive and in-depth analysis of the current research on digital payment systems. It examines and evaluates 346 journal papers from reliable sources like Scopus and Web of Science that were published between 2015 and 2023. The study intends to give readers a thorough grasp of the state of the art in the field of digital payments research, pinpoint new directions, and emphasize important issues. Among the important conclusions is a noteworthy rise in publications, especially in 2019 and 2020, which suggests that scholarly interest in this field is expanding. Leading scholarly journals that have made a substantial contribution to the conversation about digital payments are identified in the study, along with well-known writers and articles that have written extensively in the area. The study finds popular themes including electronic money, mobile payments, information technology, and digital payment systems through keyword co-occurrence analysis. These themes illustrate areas of interest within the academic community and represent the dynamic nature of research on digital payments. The overall goals of the research are to improve the body of knowledge already in existence, offer guidance for further research, and provide policymakers and other stakeholders in digital payment systems with suggestions that are supported by data. It is a useful tool for learning about the state of the field, emerging trends, and future research directions in this dynamic and growingly significant area.
Keywords: Digital Payment; Information- Technology; Mobile Banking; Policy Making; and Electronic Money